The Structure of Hungarian Medium and Large Cities - Csapó Tamás (Journal for Geography, 2006)
The functional structure of cities has been gradually transforming since the political changes. These transformations have been driven by the transition to a market economy and deurbanization processes. As a result, the functional structure of domestic large and medium-sized cities has become more similar to that of developed European cities. In cities, the share of residential function is primarily declining due to the expansion of central business districts, the construction of peripheral shopping centers, and the growth of industrial areas. While the zone of outer residential areas is expanding through the development of housing estates and the spread of single-family home areas, the area of inner residential zones is decreasing. As a result of the transition to a market economy, cities are losing their morphology. Due to the uniform construction style of multinational companies in peripheral shopping and industrial areas, it became similar to that of the similar zones of Western European medium cities. Only the historical city center and partly the inner residential area have managed to maintain their old, traditional appearance.